Apakah Saham Berlabel Syari’ah Memenuhi Kepatuhan dan Prinsip Moral Islam? (Study Kasus: Pasar Modal Syari’ah Indonesia) - Nanda Karunia Amanah; Budi Purwanto; Wita Juwita Ermawati (IPB University, 2019)
The financial industry with the principle of shari'ah compliance has grown rapidly in almost all countries in recent years. Sharia Capital Market is an important segment of sharia financial development. The Islamic capital market must adhere to the moral principles of Islam, which are free from interest (riba), masyir (gambling) which automatically avoids things that lead to gharar (uncertainty). Islamic rules clearly forbid such conditions, so that the allocation of assets to Sharia stocks in the Islamic capital market tends to be bounded based on sharia moral principles. This study intends to evaluate the level of compliance of shariaa labeled stocks against bounded moral sharia. The method used is a measure of financial ratios based on POJK No. 35 /POJK.04/2017, linkage distance sharia compliance to default (DSCD) and the rate of compliance value for all shari'ah shares incorporated in the Indonesian Syari'ah Stock Index (ISSI). The fact is that not all shares with a syari'ah label are compliant with the existing Shari'ah moral principles.